2011
DOI: 10.1111/j.1365-2125.2010.03851.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rectal ozone on the portal vein oxygenation and pharmacokinetics of propranolol in liver cirrhosis (a preliminary human study)

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• Experimental work has shown that ozone protected both the liver and kidney from reperfusion injury through release of mediators of nitric oxide. Rectal ozone increased oxygenation in the intestinal wall (250%), portal vein (134%) and liver parenchyma (127%) in experimental animals. The kinetics of propranolol and other oxidation-dependent drugs have been reported to be affected due to liver cirrhosis. Several experimental studies have reported improved propranolol clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Second, because immediate release propranolol reaches peak plasma concentration in approximately 90 minutes (Paterson et al 1970; Shand et al 1970) and has a half-life of 3–4 hours (Duchateau et al 1986; George et al 1972; Riopel and Walle 1980; Shand and Rangno 1972), it seems unlikely that appreciable levels of propranolol would have been present 24 hours post-administration when the test CCE session was performed. Furthermore, a recent study (Zaky et al 2011) employing a sample of patients with liver cirrhosis reported that an 80 mg dose of propranolol had almost completely cleared (mean plasma propranolol concentration < 10 ng mL) when measured 24 hours post-administration. Since the participants in this study had normal liver function and received a 40 mg dose, it seems very likely that propranolol had completely cleared in the 24 hours preceding the test session.…”
Section: Discussionmentioning
confidence: 99%
“…Second, because immediate release propranolol reaches peak plasma concentration in approximately 90 minutes (Paterson et al 1970; Shand et al 1970) and has a half-life of 3–4 hours (Duchateau et al 1986; George et al 1972; Riopel and Walle 1980; Shand and Rangno 1972), it seems unlikely that appreciable levels of propranolol would have been present 24 hours post-administration when the test CCE session was performed. Furthermore, a recent study (Zaky et al 2011) employing a sample of patients with liver cirrhosis reported that an 80 mg dose of propranolol had almost completely cleared (mean plasma propranolol concentration < 10 ng mL) when measured 24 hours post-administration. Since the participants in this study had normal liver function and received a 40 mg dose, it seems very likely that propranolol had completely cleared in the 24 hours preceding the test session.…”
Section: Discussionmentioning
confidence: 99%
“…We read with interest the paper by Zaky et al . [1]. In this study, the results of the propranolol pharmacokinetics in cirrhotic patients show that after 14 rectal administrations of oxygen‐ozone (300 ml of 40% ozone/oxygen mixture), all parameters of the drug's metabolism improve.…”
mentioning
confidence: 62%
“…The patient has to lie down on the back for 2 -3 minutes for better absorption. The ozone/oxygen mixture was generated from an ozone generator for medical use (O3-Ozonics generator, Ozone Forum of India), which is automated and standardized for time, volume and concentration (19).…”
Section: Methodsmentioning
confidence: 99%